THE HISTORICAL DEVELOPMENT OF THE GROUP BAMBOO CLARINET MUSIC GEMA DIRGANTARA LIWUTUNG - Millen Rousevelt Hendriks; Franklin Dumais; R. A. Dinar Sri Hartati (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This study is conducted to analyze the historical development of the Group Gema Dirgantara Liwutung as the group of bamboo clarinet music. This research uses a qualitative approach and the data collection techniques used are observation, interviews, documents. Data analysis is done after the data is collected then classified, interpreted and described in the form of words. The results of this study indicate that Bamboo Clarinet Music is the most influential art in community activities in Liwutung village. For example a wedding event, in the event Bamboo Clarinet Music plays an important role when the groom will go to the bride's house and pick her up then go to the house of worship (church) and at the peak of the wedding there is a Polynesian dance accompanied by Bamboo Music. In addition, Bamboo Music is not only used for village activities but is also often invited to various events outside the region and nationally with achievements, namely the golden Indonesia commemoration event at the State Palace in 1995, Makasar Trevel Mart in 1996, and the birthday of Jayapura city in 2015. Based on the research results, the author suggests: 1) There needs to be a forum for routine/planning performances in an event or concert, so that Bamboo Music is known more widely; 2) There needs to be successors to play bamboo music; 3) The need for regular training, so that in an event or concert the preparation is very mature.This study is conducted to analyze the historical development of the Group Gema Dirgantara Liwutung as the group of bamboo clarinet music. This research uses a qualitative approach and the data collection techniques used are observation, interviews, documents. Data analysis is done after the data is collected then classified, interpreted and described in the form of words. The results of this study indicate that Bamboo Clarinet Music is the most influential art in community activities in Liwutung village. For example a wedding event, in the event Bamboo Clarinet Music plays an important role when the groom will go to the bride's house and pick her up then go to the house of worship (church) and at the peak of the wedding there is a Polynesian dance accompanied by Bamboo Music. In addition, Bamboo Music is not only used for village activities but is also often invited to various events outside the region and nationally with achievements, namely the golden Indonesia commemoration event at the State Palace in 1995, Makasar Trevel Mart in 1996, and the birthday of Jayapura city in 2015. Based on the research results, the author suggests: 1) There needs to be a forum for routine/planning performances in an event or concert, so that Bamboo Music is known more widely; 2) There needs to be successors to play bamboo music; 3) The need for regular training, so that in an event or concert the preparation is very mature.